The original copy : photography of sculpture, 1839 to today - Marcoci, Roxana B.; Exhibition. New York. Museum of Modern Art. 2010-08,01 (New York, NY : Museum of Modern Art, 2010)
The original copy: photography of sculpture, 1839 to today / Roxana Marcoci ##An almost unlimited variety: photography and sculpture in the nineteenth century / Geoffrey Batchen ##From sculpture in photography to photography as plastic art / Tobia Bezzola ##Plates, with introductions / Roxana Marcoci ##I. Sculpture in the age of photography ##II. Eugène Atget: the marvelous in the everyday ##III. Auguste Rodin: The sculptor and the photographic enterprise ##IV. Constantin Brancusi: The studio as Groupe Mobile and the Photos Radieuses ##V. Marcel Duchamp's Box in a valise: the readymade as reproduction ##VI. cultural and political icons ##VII. The studio without walls: sculpture in the expanded field ##VIII. Daguerre's soup: what is sculpture? ##IX. The pygmalion complex: animate and inanimate figures ##X. The performing body as sculptural object.
Published in conjunction with the exhibition The original copy: photography of sculpture, 1839 to today, at the Museum of Modern Art, New York (August 1-November 1, 2010)
Onderzoek KASK (1KA-OF1001)
boek